User-centric Mental Health Solutions: Analyzing Bright’s Impact On Emotional Resilience - Ramadhan, Yumna Zahran; Kurniawan, Muhammad Aziz; Solehuddin, Muhammad; Sazkia, Adelia Chitra; Juliantara, I Putu Eka (STKIP PGRI Tulungagung, 2025)
Mental health is a fundamental aspect of human well being, yet it often faces persistent barriers such as stigma, high treatment costs, and limited access to professional psychological services. This study addresses these challenges by designing the Bright for Mental Health application, developed through the Design Thinking framework encompassing empathy, problem definition, ideation, prototyping, and evaluation. The usability of the application was assessed using the System Usability Scale–Positive (SUS-P) method. The evaluation involved user testing, which resulted in an average score of 79.7, placing the application in the “Good” usability category. This outcome suggests that the system demonstrates strong levels of effectiveness, efficiency, and user satisfaction, although certain aspects still require further refinement. By integrating AI-driven features, the application expands the potential for inclusive and accessible digital mental health support, reducing barriers to care and offering an alternative for individuals with limited access to professional services. The findings highlight the significance of combining user-centered design principles with technological innovation to create impactful digital health solutions. Future studies are recommended to engage a more diverse range of respondents and enhance collaboration with mental health professionals to strengthen the application’s effectiveness and adoption in broader communities.